Exploring hidden influences on users' decision-making: A feature-lesioning technique to assist design thinking. Issue 4 (1st October 2016) - Gleasure, Rob; O'Riordan, Sheila
Abstract: This study presents a qualitative design thinking technique to help system designers explore hidden influences on users' decision-making processes. This technique targets context-specific influences that have accumulated in the absence of conscious reflection, and hence may exist without users' awareness. Such processes may lie outside the reach of traditional discursive approaches; thus, our technique augments existing approaches with a method for 'lesioning' information sources, i.e. removing specific information sources and observing how and when users' decision-making behaviour breaks down. This deconstruction allows dependencies to be exposed, allowing a better understanding of hidden influences, which can then be assimilated into design ideation. The lesioning technique is tested and demonstrated over multiple experimental iterations in the context of Twitter, a leading social media service. These iterations present several insights and design opportunities surrounding how users determine what connections to form and how those users make sense of information on busy content feeds.